ADAPTING A PARENT‐COMPLETED, SOCIOEMOTIONAL QUESTIONNAIRE IN CHINA: THE AGES & STAGES QUESTIONNAIRES: SOCIAL‐EMOTIONAL. Issue 2 (15th February 2017) - Bian, Xiaoyan; Xie, Huichao; Squires, Jane; Chen, Chieh‐Yu
ABSTRACT: The Ages & Stages Questionnaire: Social‐Emotional (ASQ:SE; Squires, Bricker, & Twombly, 2002a), developed in the United States, was translated and adapted for use in China. Lack of valid and reliable instruments for identifying social and emotional delays in young children is a worldwide issue. Professionals in China have recently focused efforts on developing methods for early identification of social, emotional, and behavioral issues in the birth‐to‐5 population. Following the guidelines of the International Test Commission, the ASQ:SE was translated into Simplified Chinese (ASQ:SE‐C) to collect a normative sample of 2, 528 children across China. Data were analyzed to evaluate the psychometric properties of the ASQ:SE‐C, using both classical test theory and item response theory, including generating cutoff points appropriate for the Chinese sample. A panel of Chinese experts was surveyed to assess face validity and estimated utility of the newly adapted tool. Discussions of research findings and implications for future studies are provided.